Family Members’ Involvement in the Initial Individual Education Program (IEP) Meeting and the IEP Process: Perceptions and Reactions - Hammond, Helen; Ingalls, Lawrence; Trussell, Robert P. (International Journal about Parents in Education, 2023)
In view of the importance of family involvement in the process of developing a child’s initial Individual Education Program (IEP) for special education services, it is imperative for educators to be aware of possible reactions family members may experience at the onset of the process. The purpose of this study was to determine the types of reactions family members had from their initial introduction to special education services. This study involved interviewing 212 family members over a span of four years regarding their reactions and experiences when their son or daughter was initially referred to special education services. The data collected from family members were analyzed and summarized. The results of the study indicated family members experienced a variety of both negative and positive reactions to the initial IEP meeting. Implications for educators and school personnel are discussed.